Pengaruh Penanaman Nilai-Nilai Karakter terhadap Kepribadian Peserta Didik - Fitri Handayani; Kanaya Ledy Adinda; Kurnia Febriyola (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Character education has a role to shape the personality of individuals, especially the younger generation. Character is defined as behavioral values that include relationships with God, self, others, the environment, and nationality. Character education involves creating a school environment that supports the ethical and responsible development of students through modeling and teaching character. The importance of character education is recognized in the context of personality formation and positive contribution to the environment. The function of character education involves the formation and development of potential, prevention of norm-violating behavior, self-development, self-empowerment, and strengthening of identity. Teachers play a key role in the implementation of character education, with modeling, teaching and reinforcement as the main strategies. Strengthening character education is expected to produce individuals who are not only academically intelligent but also have strong moral values, creating a generation that is balanced in knowledge, attitudes, and skills in the era of industrial revolution 4.0 and social 5.0.